KKM PPM- INOVASI PANGAN LOKAL DENGAN PEMANFAATAN TEKNOLOGI AKUAPONIK BUDIDAYA IKAN DAN TANAMAN SAYUR-SAYURAN DI DESA DANDANG KECAMATAN CISAUK KABUPATEN TANGERANG, BANTEN - Alimuddin, Alimuddin; Sulaeman, Fatah (Jurnal BALIRESO, 2020)
KKN-PPM is a form of education by providing learning experiences for students to live in themidst of the community, in this case the community in particular in the community of DangdangVillage, Cisauk District, Tangerang Regency. Implementation is structured through several stagesincluding preparation, briefing, observation to the evaluation stage. Preparation is the initial stagebefore KKN-PPM is carried out, preparation for implementation and monitoring. In implementingKKN-PPM in Dangdang Village, Cisauk District, Tangerang Regency, students are expected to beable to provide thought, energy, and knowledge assistance in planning and implementingprograms that are in accordance with local conditions. Specifically KKN-PPM can make a realcontribution to the Village Dangdang, Cisauk District, Tangerang Regency in various fields ofscience. In accordance with the theme of the implementation of this KKN-PPM, the fields ofscience that can be provided are such as economics, agriculture, technology, education, as well asin other fields. The specific program is a local food innovation FGD by utilizing AquaponicsTechnology in Dangdang Village, Cisauk District, Tangerang Regency